Relationship between humus condition indicators and mobility of heavy metals in chernozems - Degtyarjov, V.V.; Chekar, O.Yu. (AgroChemistry and Soil Science, 2020)
The special role of humus substances in the absorption and retention of heavy metals is an important area of research. The aim was to establish a correlation between the content of the mobile forms of some heavy metals and the parameters of soil humus indicators, in particular to investigate the role of active humus in regulating the mobility of heavy metals in the soil. The studied indicators: the total humus content (according to Tyurin); the content of the actual humus substances and detritus (semi-decomposed, lost anatomical structure of organic remains) (according to Springer); the content of active humus (this is the part of humus that can be peptized due to the replacement of metabolically absorbed calcium in the soil by sodium) and passive humus (that is not peptized after complete removal of calcium), the content of the actual humus substances in the composition of passive humus) (according to Sokolovsky). Investigated mobile forms of heavy metals (extraction with ammonium acetate buffer pH 4,8): zinc; cadmium; nickel; cobalt; iron; manganese; lead; cuprum. The research sites: (1) chernozem typical (Calcic Voronic Chernozem SiL UE1) on the territory of the «Mykhailivska tsilyna» (Sumy region); land use options: absolute virgin land; burnt-out virgin land; forest belt; fallow land; arable; (2) chernozem typical (Calcic Voronic Chernozem CL UE1) at the experimental field in Kharkiv region - Rogan station; options: fallow land, forest belt, arable land: (a) unfertilized; (b) the mineral system; (c) organo-mineral system. Correlation analysis was performed to identify the dependence of the content of mobile forms of heavy metals on the indicators of the humus state separately in two soil layers (0-10 and 10-20 cm). In the layer of 0-10 cm for «Mykhailivska tsilyna» in all investigated land use options the content of mobile forms of manganese, cuprum, zinc, cadmium, iron is most closely connected with separate components of humus, at the same time. In the soil of Rogan station in layer 0-10 cm the closest relationship can be traced between humus and the content of mobile forms of cuprum, zinc, cobalt and lead. On the contrary, in a layer of soil of 10-20 cm other features were shown. Significantly more heavy metals were extracted from soil samples from which active humus had been previously removed than from conventional samples. This is an argument that active humus inhibits the transition of heavy metals into the soil solution, ie, reduces the mobility of heavy metals and accessibility to plants. This phenomenon is called the "blocking function" of active humus.